Expanded evidence that the 31-gene expression profile test provides clinical utility for melanoma management in a multicenter study. (3rd August 2022) - Dillon, Larry D.; McPhee, Michael; Davidson, Robert S.; Quick, Ann P.; Martin, Brian; Covington, Kyle R.; Zolochevska, Olga; Cook, Robert W.; Vetto, John T.; Jarell, Abel D.; Fleming, Martin D.
Abstract: Objective: National Comprehensive Cancer Network (NCCN) guidelines for cutaneous melanoma (CM) recommend physicians consider increased surveillance for patients who typically have lower melanoma survival rates (stages IIB-IV as determined by the American Joint Committee on Cancer (AJCC), 8th edition). However, up to 15% of patients identified as having a low recurrence risk (stages I-IIA) experience disease recurrence, and some patients identified as having a high recurrence risk will not experience any recurrence. The 31-gene expression profile test (31-GEP) stratifies patient recurrence risk into low (Class 1) and high (Class 2) and has demonstrated risk-appropriate impact on disease management and clinical decisions. Methods: Five-year plans for lab work, frequency of clinical visits, and imaging pre- and post-31-GEP test results were assessed for a cohort of 509 stage I-III patients following an interim subset analysis of 247 patients. Results: After receiving 31-GEP results, 50.6% of patients had a change in management plans in at least one of the following categories—clinical visits, lab work, or surveillance imaging. The changes aligned with the risk predicted by the 31-GEP for 76.1% of patients with a Class 1 result and 78.7% of patients with a Class 2 result. A Class 1 31-GEP result was associated with changes toward low-intensity management recommendations, while a Class 2 result was associated with changes toward high-intensity management recommendations. Conclusion: The 31-GEP can stratify patient recurrence risk in patients with CM, and clinicians understand and apply the prognostic ability of the 31-GEP test to alter patient management in risk-appropriate directions. PLAIN LANGUAGE SUMMARY: When caught early, cancer of the skin can usually be removed, and patients have excellent chances of survival. However, some patients will have their cancer come back or spread to a new location in their body. The 31-gene expression profile (GEP) test measures the expression levels of 31 genes from an individual patient's tumor. A proprietary formula uses this information to identify the risk of recurrence or spread as low risk (Class 1) or high risk (Class 2). Cancers with low-risk 31-GEP scores have a lower chance of cancer recurrence or spread than patients with a high-risk score. In this study, we wanted to determine if doctors treated patients with low-risk scores differently from patients with high-risk scores. We found that doctors changed approximately half of patient treatment plans (doctor visits, lab work, or imaging to see if the cancer has come back) after learning the 31-GEP test results. Doctors usually planned less frequent follow-up visits for Class 1 results and more frequent follow up for Class 2 results. This study found doctors understand and make changes to their treatment plans based on the patient's 31-GEP test result.